2022
DOI: 10.7759/cureus.25421
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis and Thrombocytopenia: A Nowadays Problem

Abstract: Sepsis is a life-threatening organ failure produced by a dysregulated host response to infection that involves 15.6% of hospital mortality. The most common signs and symptoms of sepsis are hypotension, tachypnea, fever, and leukocytosis, whether suspected or confirmed. Including a major one, thrombocytopenia is a sign that is an independent predictor of poor outcomes in patients with sepsis, increasing their mortality rate and their length of stay in the intensive care unit (ICU). So far, the ongoing treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Patients who had both thrombocytopenia and lymphopenia were more likely to suffer from hematooncological conditions (15/107 [14%] vs. 3/308 [0.9%], p = 0.00), and subsequently, the age-adjusted Charlson's score was higher (median 6 [4][5][6][7][8] vs. 5 [3][4][5][6][7], p = 0.00). At admission, more patients with both thrombocytopenia and lymphopenia required respiratory support (both any and significant support) ( [3.4-7.9] vs. 8.9 [5.9-11.5] cells/μL, and 11.3 ± 2.5 vs. 12.2 ± 2.4 mg/dL, mean SD, respectively, p < 0.05 for all comparisons).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who had both thrombocytopenia and lymphopenia were more likely to suffer from hematooncological conditions (15/107 [14%] vs. 3/308 [0.9%], p = 0.00), and subsequently, the age-adjusted Charlson's score was higher (median 6 [4][5][6][7][8] vs. 5 [3][4][5][6][7], p = 0.00). At admission, more patients with both thrombocytopenia and lymphopenia required respiratory support (both any and significant support) ( [3.4-7.9] vs. 8.9 [5.9-11.5] cells/μL, and 11.3 ± 2.5 vs. 12.2 ± 2.4 mg/dL, mean SD, respectively, p < 0.05 for all comparisons).…”
Section: Resultsmentioning
confidence: 99%
“…Thrombocytopenia is common in critically ill patients and it is an independent risk factor for mortality in intensive care (ICU) patients. Sepsis-associated thrombocytopenia has been recognized for many years as a predictor of adverse outcomes [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Early recognition and prompt treatment of sepsis in burn patients are vital to improving their outcomes and reducing the risk of complications [ 35 ]. The proposed mechanisms of thrombocytopenia in sepsis consist of decreased production of platelets due to bone marrow failure, especially because of antibiotics and proton pump inhibitors [ 36 , 37 ], immune-associated thrombocytopenia due to the presence of platelet autoantibodies [ 38 ] or an unrestrained proliferation and activation of monocytes and macrophages that act as hemophagocytes [ 39 ], increased platelet sequestration in microvessels [ 39 ], disseminated intravascular coagulation with excessive consumption of platelets in sepsis [ 40 ], and hemodilution during massive crystalloid or colloid perfusion or blood product transfusions [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies reviewed consist of case reports that demonstrate a concurrent or reciprocal causal relationship between the two conditions, suggesting a strong association [ [23] , [24] , [25] ]. Thrombocytopenia has been found to be linked with compromised immune function, as evidenced by its prevalence among sepsis patients [ 26 ]. Furthermore, the severity of thrombocytopenia has been positively correlated with the severity of sepsis [ 26 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Thrombocytopenia has been found to be linked with compromised immune function, as evidenced by its prevalence among sepsis patients [ 26 ]. Furthermore, the severity of thrombocytopenia has been positively correlated with the severity of sepsis [ 26 ]. It was reported that a patient with end-stage renal disease developed thrombocytopenia, and phlegmonous gastritis occurred after ESD surgery [ 6 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%